Femoral bone microstructure in 1-month-old non-transgenic versus transgenic rabbits with the WAP-hFVIII gene construct - Martiniaková, Monika; Omelka, Radoslav; Grosskopf, Birgit; Smoláriková, Vladimíra; Bauerová, Mária; Chrenek, Peter (Folia biologica (Praha), 2008)
Differences in microscopic structure of the femur between 1-month-old transgenic rabbits carrying the hFVIII gene and non-transgenic rabbits were investigated. Bone microstructure was evaluated from the point of view of qualitative and quantitative histological characteristics. We identified fibrolamellar bone tissue only in the transgenic animals. Measured values for area, perimeter of the Haversian canals and minimum diameter of the primary osteons' vascular canals were higher in 1-month-old transgenic individuals (P < 0.05; P < 0.001). We also observed lower concentrations of Ca, P, K, solids, and total mineral content in femora of transgenic rabbits. A statistically significant difference was observed for the concentration of Ca (P < 0.05). Our results indicate evident changes in both qualitative and quantitative histological characteristics of the femur, which result especially in better blood supply and slightly reduced mineralization process in 1-month-old transgenic rabbits.
Keywords: Rabbits; faktor VIII; novorozená zvířata; Humans; mléčné bílkoviny; Milk Proteins; Calcification, Physiologic; zvířata; Animals, Genetically Modified; Animals, Newborn; Femur; Factor VIII; mužské pohlaví; femur; kostní denzita; ženské pohlaví; Animals; fyziologická kalcifikace; geneticky modifikovaná zvířata; lidé; králíci; Bone Density; Male; Female